Teaching English in Primary School through a Spiral Thematic Curriculum - Cadavid, Cristina (Íkala, Revista de Lenguaje y Cultura, 2003)
This article presents an experience of implementing a spiral thematic curriculum to teach English in a public primary school in Medellin. The design and implementation of this curriculum are part of an action research project that focuses on determining the effects of using it to teach English to children from kindergarten to fifth grade. The project involved the participation of a teacher from the primary school, six student teachers from theUniversidad de Antioquia who are doing their practicum there, and the university advisor. The findings of this research were twofold: the children were involved in the process of learning a foreign language in a meaningful way, and their teachers (the student teachers) discovered a way to approach their task from a more student-sensitive and reflective perspective. Received: 19-12-02 / Accepted: 20-05-03 How to reference this article: Cadavid, C. (2003). Teaching English in Primary School through a Spiral Thematic Curriculum. Íkala. 8(1), pp. 81 – 97